Features of the duties caused by the person in the case of the realization of his right to self-defense - Ляшевська, Л. І. (Problems of legality, 2013)
Peculiarities of the duties on compensation of the harm caused by a person in the realization of his right to self-defense. The article deals with the analysis of the elements on compensation of the harm caused by a person in the realization of his rights to self-defense. The characteristic features of the duties on compensation of this harm, the grounds and conditions of their emergence are established. It is stressed that the specifics of such duties (subjective condition) are the lack of guilt in the causer of the harm as self-defense is a lawful act.